Advances in theoretical and experimental research of high temperature cuprate superconductivity (World Scientific, 2020)
"Researchers working at the frontier of high-Tc Superconductors have reviewed the development in this area in the past 20 years. Both experimental and theoretical aspects have been covered. New directions and possible theoretical models were suggested. The contributors of this book are from China Center of Advanced Science and Technology (CCAST); Institute of Physics Chinese Academy of Sciences (CAS); National Lab for Superconductivity, Institute of Physics, CAS; School of Physics, Peking University and Center of Advanced Study Tsinghua University. This volume will be a useful guide to those who are working in the field"--Publisher's website
Keywords: Copper oxide superconductors / Congresses; High temperature superconductors / Congresses; High temperature superconductivity / Congresses